2010
DOI: 10.1001/jama.2010.1192
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioral Therapy vs Relaxation With Educational Support for Medication-Treated Adults With ADHD and Persistent Symptoms

Abstract: Context Attention-deficit/hyperactivity disorder (ADHD) in adulthood is a prevalent, distressing, and impairing condition that is not fully treated by pharmacotherapy alone and lacks evidence-based psychosocial treatments.Objective To test cognitive behavioral therapy for ADHD in adults treated with medication but who still have clinically significant symptoms. Design, Setting, and PatientsRandomized controlled trial assessing the efficacy of cognitive behavioral therapy for 86 symptomatic adults with ADHD who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
229
2
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(251 citation statements)
references
References 17 publications
(24 reference statements)
12
229
2
8
Order By: Relevance
“…However, these studies are limited by small samples sizes and lack of control groups and in recent years randomised controlled trials (RCTs) have begun to emerge (e.g. Emilsson et al, 2011;Safren et al, 2010;Stevenson, Whitmont, Bornholt, Livesey, & Stevenson, 2002).…”
mentioning
confidence: 99%
“…However, these studies are limited by small samples sizes and lack of control groups and in recent years randomised controlled trials (RCTs) have begun to emerge (e.g. Emilsson et al, 2011;Safren et al, 2010;Stevenson, Whitmont, Bornholt, Livesey, & Stevenson, 2002).…”
mentioning
confidence: 99%
“…Randomized studies found a significant effect of CBT in adult ADHD patients, and this effect lasted for 12 months (64). There are no studies yet to show if this treatment, which is known to be effective in SUD as well, is also effective in comorbidity of both disorders.…”
Section: Effect Of Psychotherapymentioning
confidence: 99%
“…108 The best evidence comes from a trial conducted by Safren et al 109 The study enrolled 86 adults with ADHD who were already being prescribed medication and randomized them to cognitive behavioral therapy or relaxation with attentional support. Cognitive behavioral therapy was associated with greater improvement in ADHD symptoms -with improved scores in the ADHD-rating scale, Clinical Global Impression severity, and self-report ADHD scale -, and the benefits were maintained after 12 months of follow-up.…”
Section: Treatment Of Adultsmentioning
confidence: 99%